Influencer Marketing and Online Advertising as A Digital Marketing: A Case Study Green Beauty Products - Yusiana, Rennyta; Hurriyati, Ratih; Dirgantari, Puspo Dewi; Disman, Disman (Jurnal Manajemen Indonesia, 2023)
The beauty industry in Indonesia is experiencing rapid growth, driven by factors such as a large young population and increasing purchasing power. The government is also encouraging improvements in the supply chain of raw materials to increase the national added value. Additionally, advancements in technology and the rise of social media and digital platforms have provided opportunities for the promotion and dissemination of beauty products. Influencer marketing and online advertising have become popular strategies for promoting beauty products. These techniques have been found to have a positive impact on consumer purchase decisions. Green brand knowledge has also gained importance in the beauty industry, as consumers are becoming more conscious of environmental issues and seeking sustainable and eco-friendly products. Therefore, this study aims to examine the impact of influencer marketing, online advertising, and green brand knowledge on the purchase decisions of green beauty products. The study utilizes a quantitative research approach and analyses data from 100 consumers. The findings suggest that influencer marketing and online advertising, have a direct impact on purchasing decisions, while green brand awareness has an insignificant impact on purchase decisions. The study recommends that companies focus on creating high-quality influencer content and implementing effective online marketing strategies to enhance the impact of these techniques. Additionally, companies should choose influencers and platforms aligned with their target audience. The study acknowledges limitations in sample size and research method and suggests further research to validate the findings. Keywords—Influencer Marketing; Online Advertising; Green Brand Knowledge; Purchase Decision